Exercise Intensity May affect Bdnf Level in the Hippocampus of Fructose-Induced Mice - Misbakhul Munir; Muhammad Miftahussurur; Adi Pranoto; Purwo Sri Rejek (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction – Several studies show that there is a negative correlation between obesity and cognitive function. Exercise can reverse the bad effect of obesity through mediation of BDNF. Research about the effect of exercise intensity to BNDF levels in hippocampus of mice is ever be done, but research about the effect of exercise intensity to BNDF levels in hippocampus of fructose-induced mice is never be done.Objective – To prove the effect of different exercise intensity to BDNF level in hippocampus of fructoseinduced mice. Methods – A total of 32 mice were divided into four groups: Control group which was a CON and treatment groups which were low-intensity exercise (LIE), moderate-intensity exercise (MIE), and high-intensity exercise (HIE). The duration of treatment was 4 weeks. Swimming to exercise held 3 times a week and fructose solution dose was 270 grams for 9 days.Results – This research revealed that there was significantly difference on body weight before and after administration of fructose solution for 9 days (p=0.000). The lowest BDNF levels after treatment was group C and the highest of BDNF levels was group MI. There was no significantly difference in BDNF levels among groups after treatment (p=0.378), but there was tendency for BDNF levels to increase with exercise intensity.Conclusion – Swimming exercise with low-intensity, moderate-intensity, and high intensity has no effect on BDNF level in the hippocampus of fructose-induced mice.